Features of Syntagmatic Associations for Stimuli-Names of Food Products in Ukrainian and Modern Greek Languages - Petrova, Galyna (East European Journal of Psycholinguistics, 2017)
500 respondents who are Ukrainian native speakers and 100 Modern Greek speakers participated in free word association test held in March and July, 2015 in Kyiv, Ukraine, and in Athens, Greece. The data were calculated as to the frequency of responses and composed a field of associations for each stimulus. The classification of associations to the word-stimuli “food products” was based on existing classifications and on the specific of the test material. In this paper, the authors discuss the syntagmatic type of associations expressed by adjectives that represent the objective characteristics of the product and form a phrase with a word-stimulus (Terekhova, 2000). They can be roughly divided into 2 groups of associating directions: features of product attributes (52 % of all syntagmatic associations in Ukrainian language (hereinafter – UL) and 41% in Modern Greek (hereinafter – MGL)) and feautures of stages that the product passes (UL – 41%, MGL – 48 %). Some differences in quantitative and qualitative aspects were found during the determination of associating directions within the syntagmatic type of associations: different percentage of responses in associating directions in quantitative aspect. As to the quality, the differences lay in determination of feature directions in the languages. Thus for the associative field of Modern Greek language, the reactions that characterize the form of the product have not been found at this stage yet. Асоціативний словник української рекламної лексики / уклад. Т. Ю. Ковалевська,Г. Д. Сологуб, О. Г. Ставченко. Одеса: Астропринт, 2001.Asotsiatyvnyi Slovnyk Ukrainskoyi Reklamnoyi Leksyky [Associative Dictionary ofUkrainian Advertising Vocabulary] (2001). T. Kovalevska. H. Sologub, O. Stavchenko,(eds.). Odesa: Astroprint. Бутенко Н. П. Словник асоціативних норм української мови. Львів: Вища школа,1979.Butenko, N. (1979). Slovnyk Asotsiatyvnykh Norm Ukrainskoyi Movy [Dictionary ofAssociative Norms of the Ukrainian Language]. Lviv: Vyshcha Shkola. Бутенко Н. П. Словник асоціативних означень іменників в українській мові. Львів:Вища школа, 1989.Butenko, N. (1989). Slovnyk Asotsiatyvnykh Oznachen Imennykiv v Ukrainskiy Movi[Dictionary of Associative Definitions of Nouns in the Ukrainian Language]. Lviv:Vyshcha shkola. Горошко Е. И. Интегративная модель свободного ассоциативного эксперимента. Х.;М.: РА-Каравелла, 2001.Goroshko, Ye. (2001). Integrativnaya Model Svobodnogo Assotsiativnogo Eksperimenta[Integrative Model of Free Associatiation Test]. Kharkiv; Moscow: Russian Academy ofSciences–Karavella. Мартінек С. В. Український асоціативний словник. Львів: Видавничий центр ЛНУімені Івана Франка, 2007.Martinek, S. (2007). Ukrainskyi Asotsiatyvnyi Slovnyk [Ukrainian Associative Dictionary].Lviv: Ivan Franko National University of Lviv.Марфіна Ж. В. Мовна асоціація як об’єкт наукового вивчення [Електронний ресурс].Режим доступу: http://www.vuzlib.com.ua/articles/book/4258.html.Marfina, Zh. Movna asotsiatsiia yak obiekt naukovoрo vyvchennia [Language associationas an object of scientific study]. Retrieved from:http://www.vuzlib.com.ua/articles/book/4258.htmlПатсис М. Специфика ассоциативного поля слова в греческом языке. Вопросыпсихолингвистики. 2004, №2. С. 91–97.Patsis, M. (2004). Specifika associativnogo polia slova v grecheskom yazyke [Specificityof the Associative Field of a Word in the Greek language]. Voprosy Psikholingvistiki, 2,91–97.Серкин В. П. Психосемантика [Електронний ресурс]. Режим доступу:http://stud.com.ua/43612/psihologiya/asotsiativni_eksperimenti#66Serkin V. Psykhosemantika [Psychosemantics]. Retrieved from: http://stud.com.ua/43612/psihologiya/asotsiativni_eksperimenti#66Славянский ассоциативный словарь: русский, белорусский, болгарский, украинский /Под ред. Н. В. Уфимцевой, Г. А. Черкасовой, Ю. Н. Караулова, Е. Ф. Тарасова. М.,2004.Slavianskii Assotsiativnyi Slovar: Russkiy, Beloruskiy, Bolgarskiy, Ukrainskiy [SlavicAssociative Dictionary: Russian, Belarusian, Bulgarian, Ukrainian]. (2004).N. Ufimtseva, G. Cherkasovа, Yu. Karaulov, Ye. Tarasov, (eds.). Moscow.Терехова Д. І. Особливості сприйняття лексичної семантики слів (психолінгвістичний аспект). К.: Київський державний лінгвістичний університет, 2000.Terekhova D. (2000). Osoblyvosti Spryiniattia Leksychnoyi Semantyky Sliv(Psykholinhvistychnyi Aspekt) [Peculiarities of Perceiving Lexical Semantics of Words(Psycholinguistic Aspect)]. Кyiv: Kyiv State Linguistic University.